Augmented Reality system for Immersive Mobile Robot Simulation and Trajectory Estimation - Birais, Pedro Henrique; Rafikova, Elvira (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
In augmented reality (AR) applications, the real world can interact with the virtual world through image processing and overlay. This concept is increasingly being utilized in various Industry 4.0 applications, such as mobile robotics, the Internet of Things, computer vision, and more. This article presents the development of an augmented reality (AR)-based digital twin system with a focus on its educational significance. The developed system enables simulation, interaction, and real-time visualization of the trajectory of an autonomous mobile robot, using sensor fusion with the Kalman filter. By integrating AR with the robot's odometry, the system enhances the accuracy of robot localization, providing an immersive and interactive learning experience. Leveraging AR software development kits like Unity and Vuforia facilitated the creation of a modular application that can be used in conjunction with a mobile robot. The effectiveness of the developed system is demonstrated by delivering enhanced reliability and precision in estimating the robot's trajectory, thereby contributing to a better understanding of autonomous locomotion principles. Furthermore, the article discusses the educational applications and ongoing improvements of the platform, exploring the potential of augmented reality as a powerful educational tool in the context of mobile robotics. Index Terms–Augmented reality. mobile robotics, digital twin, educational applications.